Penerapan Model Project Based Learning untuk Meningkatkan Hasil Belajar Peserta Didik pada Tema Pertumbuhan dan Perkembangan Makhluk Hidup Kelas III SD Negeri 208/X Simpang Tuan Semester Ganjil Tahun Ajaran 2022/2023 - Sri Ajem (Journal on Education, 2022)
The quality of education will not be separated from the professional responsibility of educators in learning. In order to achieve learning objectives that are active, innovative, creative, effective, and enjoyable, each educator prepares a learning strategy with all its supporting elements, including learning media. The purpose of this study was to obtain information and discuss the application of the project based learning model to improve student learning outcomes on the theme of growth and development of living things in class III SD Negeri 208/X Simpang Tuan odd semester 2022/2023 Academic Year. This research is a classroom action research which consists of two cycles where each cycle consists of two meetings. Each cycle follows four stages, namely planning, implementing, observing, and reflecting. The research was carried out at SDN 208/X Simpang Tuan in the odd semester of the 2022/2023 academic year with 28 class III students as research subjects. Data collection techniques using tests, observations, field notes and documentation. Data were analyzed using percentages and data reduction. Based on the results of the research and discussion it can be concluded that based on the results of the research and discussion it can be concluded that through the application of the project based learning model it can improve student learning outcomes on the theme of growth and development of living things in class III SD Negeri 208/X Simpang Tuan odd semester 2022 academic year /2023 with the act of giving rewards